Effectiveness of e-Procurement, Regulations, and Supervision on Transportation Subcontract Performance: The Mediating Role of Subcontract Governance at PT Pos Indonesia - Mujiyono Mujiyono; Maniah Maniah; Agus Purnomo (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the effects of e-Procurement efficiency, regulatory compliance, and supervision on transportation subcontractor performance, as well as to examine the mediating role of transportation subcontract governance at PT Pos Indonesia (Persero). A quantitative approach was employed using Structural Equation Modeling with Partial Least Squares (PLS-SEM) to test both direct and indirect relationships among variables. Data were collected through a census survey of 120 respondents from hub offices directly involved in managing and supervising transportation subcontractors. The results indicate that e-Procurement efficiency and supervision have a positive and significant effect on transportation subcontractor performance, while regulatory compliance does not have a direct effect on performance. However, regulatory compliance (β=0.512, p<0.001) and supervision (β=0.343, p<0.001) significantly influence transportation subcontract governance, which in turn positively and significantly affects subcontractor performance (β=0.320, p=0.002). Furthermore, subcontract governance mediates the effects of regulatory compliance (β=0.164, p=0.009) and supervision (β=0.110, p=0.013) on performance, but does not mediate the effect of e-Procurement efficiency. These findings suggest that strong governance mechanisms are critical in translating regulatory and supervisory efforts into improved subcontractor performance.